2006
DOI: 10.1614/ws-05-118r.1
|View full text |Cite
|
Sign up to set email alerts
|

Weed management systems in Indiana tomato production

Abstract: The influence of management practices at a system level is rarely studied in weed science, even though weed communities respond to the cumulative effect of farm management systems. On-farm visits and detailed grower surveys were used to objectively classify 59 Indiana tomato fields into management systems. Fields were chosen to represent a range of practices used to grow conventional and organic tomatoes. Multivariate statistical analyses identified five distinct management systems based primarily on differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
(28 reference statements)
0
9
0
1
Order By: Relevance
“…Additionally, the time, labor, and fuel required for mechanical weed control is a significant contributor to total production costs in organic cropping systems (Archer et al 2007). For example, compared with conventional production, time spent hand weeding was almost double in organic fresh market tomato ( Solanum lycopersicum L.) production (Hillger et al 2006), and on-farm fuel costs were almost double in organic soybean [ Glycine max (L.) Merr.] production (McBride and Greene 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the time, labor, and fuel required for mechanical weed control is a significant contributor to total production costs in organic cropping systems (Archer et al 2007). For example, compared with conventional production, time spent hand weeding was almost double in organic fresh market tomato ( Solanum lycopersicum L.) production (Hillger et al 2006), and on-farm fuel costs were almost double in organic soybean [ Glycine max (L.) Merr.] production (McBride and Greene 2009).…”
Section: Introductionmentioning
confidence: 99%
“…O Brasil destaca-se como um dos maiores produtores dessa cultura, considerando a produção destinada à indústria, com área colhida de aproximadamente 55.000 hectares e uma produção de cerca de 3.200.000 toneladas, atingindo a produtividade de 58.000 kg ha -1 em 2007 (AGRIANUAL, 2008). Entretanto, o tomateiro está sujeito à interferência negativa de plantas daninhas que competem por nutrientes, água e luz e podem causar sérios prejuízos à cultura, reduzindo assim sua produtividade (NASCENTE et al, 2004;HILLGER et al, 2006).…”
Section: Introductionunclassified
“…and as a result reduce yield (Buckelew et al 2006;Garvey et al 2013). Herbicides, cultivation (in bareground tomato), hand weeding, mulch, and crop rotation are techniques used for weed management in tomato (Hillger et al 2006). It has been shown that crop rotation (with soybean, corn, or both) can improve yield and N fertilization (Seliga and Shattuck 1995) and have a positive effect in weed management (Bond and Grundy 2001).…”
mentioning
confidence: 99%